2021
DOI: 10.3389/fpsyt.2021.680890
|View full text |Cite
|
Sign up to set email alerts
|

Poor Sleep and Decision-Making Disturbance Are Associated With Suicidal Ideation in Pre-natal Depression

Abstract: Although many risk factors for suicidal ideation have been identified, few studies have focused on suicidal ideation and pre-natal depression. The purpose was to investigate the relationship between decision-making (DM) dysfunction and sleep disturbance on suicidal ideation in pre-natal depression. Participants included 100 women in the third trimester of pregnancy, including pregnant women with pre-natal depression who had recent suicidal ideation (n = 30), pre-natal depression without SI (n = 35) and healthy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 79 publications
0
9
0
2
Order By: Relevance
“…They found that the first group reported more depression and anxiety and were more likely to endorse SI than the second group. Lastly, Bao et al ( 35 ) found that SI correlated with subjective sleep quality, duration, and daytime dysfunction among 100 pregnant women in the third trimester. It was also found that women who suffered from depression and SI indicated significantly poorer sleep quality than women who suffered from depression without SI.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that the first group reported more depression and anxiety and were more likely to endorse SI than the second group. Lastly, Bao et al ( 35 ) found that SI correlated with subjective sleep quality, duration, and daytime dysfunction among 100 pregnant women in the third trimester. It was also found that women who suffered from depression and SI indicated significantly poorer sleep quality than women who suffered from depression without SI.…”
Section: Resultsmentioning
confidence: 99%
“…Thirty-six studies of 26,035 participants reported present or past psychopathology as a risk factor for suicidality during pregnancy and the postpartum period. Most studies, reported that present or past depression ( 21 , 32 , 34 , 35 , 40 42 , 46 , 48 , 49 , 51 , 53 67 ), anxiety ( 34 , 38 , 45 , 48 , 53 , 58 , 63 ), and past suicidality ( 45 48 , 53 , 54 ) are significant risk factors for suicidality during pregnancy and the postpartum period. While two referred to psychiatric comorbidity as a significant risk factor ( 22 , 68 ), two studies referred to family psychopathology as such a factor ( 47 , 68 ).…”
Section: Resultsmentioning
confidence: 99%
“…A range of cognitive factors was investigated in seven studies ( 54 , 63 , 64 , 82 , 90 92 ). These studies’ methodological quality ratings ranged from 33 to 71%, with six of the seven studies considered “good” quality and one study was of “moderate” quality.…”
Section: Resultsmentioning
confidence: 99%
“…In a sample of 100 pregnant women, the association between decision-making function, assessed using the Iowa Gambling Task ( 93 ) and self-harm ideation was investigated ( 90 ). The participants were allocated to one of three groups: those who reported self-harm ideation, those who scored highly for depressive symptoms on the EPDS ( 33 ), but reported no self-harm ideation, and those who reported no self-harm ideation and did not score highly on the EPDS .…”
Section: Resultsmentioning
confidence: 99%
“…Restricția somnului poate duce la o perturbare a neuroplasticității, declanșând astfel unele dintre mecanismele fiziopatologice responsabile de dezvoltarea depresiei [20].…”
Section: Complicațiiunclassified